Experts outline ways to decrease the decade-long yearly rate of 40,000 new HIV infections in the US. - Copenhaver, Michael M; Fisher, Jeffrey D (AIDS and behavior, 2006)
This paper presents data from a brief, anonymous, open-ended survey of 50 behavioral research experts in HIV prevention. Responses were received from 31 participants who provided input regarding the primary reasons they believe the rate of the HIV epidemic in the United States has persisted in recent years, and how they believe we can most efficiently decrease the current rate of new HIV infections in the United States. Four clusters of reasons suggested for the persistent rate of new infections: Intervention level reasons, Society level reasons, Person level reasons, and Multiple Risk Factor reasons. Three clusters of strategies suggested for decreasing the current rate: Improved Targeting of HIV Prevention efforts, Larg-Scale Changes to HIV prevention, and Integrating HIV Prevention into more aspects of society. Results are reviewed with the objective of providing a fresh perspective on the potential means for addressing the current HIV epidemic.
Keywords: Adolescent; Adult; Behavioral Research; Disease Outbreaks; Female; HIV Infections; Humans; Incidence; Male; Middle Aged; Prevalence; Preventive Health Services; Questionnaires; Risk Reduction Behavior; Time Factors; United States